Habits of Mind Calon Guru Matematika dalam Pemecahan Masalah Matematis - Ahmad Dzulfikar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Habits of mind had the impact toward mathematical problemsolving skills, especially for the pre-service teacher who will facilitate the development of their students’ mathematical problem solving skills in the future. This qualitative descriptive study aimed to analyze mathematical problem solving habits of mind of the pre-service teacher. 22 undergraduate students were the research subject that was chosen by purposive sampling technique. The research instrument was habits of mind scale, interview guide, and mathematical problemsolving test. The study found that level of mathematical problem solving habits of mind of the pre-service teacher was apprentice and practitioner. Based on the indicators, habits of thinking flexibly had the largest frequency of subject who had novice level. Whereas, flexibility in choosing and using strategy determined whether the subject could solve the problem or not. This research hypothesized that this condition was affected by prior mathematical ability. Therefore, future research and development of mathematical problem solving habits of mind of the pre-service teacher were needed.